Inequity in healthcare utilization: analysis of the Nigeria situation (2016)
This paper analysis the extent of inequity in the utilization of healthcare services in Nigeria, and the determinants of healthcare utilization inequity. Applying the concept of horizontal inequity, the paper used the Nigeria Living Standard Survey (NLSS) 2010 data set to investigate the disproportionality in healthcare utilization. The result shows that inequity in utilization of healthcare in the country is generally skewed against the poor, as the analysis established evidence about the poor with similar medical needs as the rich having access to lesser healthcare service. The observed inequality in utilization of healthcare is mainly driven by the differences in health expenditure, residence location (rural or urban), and morbidity rate. The utilization rate of healthcare services is found to be positively related to household expenditure It is recommended that government should intensify greater equity measure to guarantee healthcare to all with minimal discrimination. While the private facilities may not be attracted to rural area, due to weak patronage arising from the poor economic fortune of the people, government will be in better position to argument and fill the deficiency gap in the rural area. Utilization of healthcare services, especially by rural dwellers can be promoted by establishing more health facilities in the rural areas.